2004
DOI: 10.1037/0735-7044.118.6.1225
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Lesions Impair Context-Related Cingulothalamic Neuronal Patterns and Concurrent Discrimination Learning in Rabbits (Oryctolagus cuniculus).

Abstract: Cingulothalamic neurons develop topographic patterns of cue-elicited neuronal activity during discrimination learning. These patterns are context-related and are degraded by hippocampal lesions, suggesting that hippocampal modulation of cingulothalamic activity results in the expression of the patterns, which could promote the retrieval of context-appropriate responses and memories. This hypothesis was tested by training rabbits (Oryctolagus cuniculus) with fornix lesions concurrently on two discrimination tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 58 publications
10
47
0
Order By: Relevance
“…In this way, the hippocampus could bias the behavioral expression systems of the brain . These results support context processing accounts of hippocampal function (Hirsh, 1974;Penick and Solomon, 1991;Kim and Fanselow, 1992;Phillips and LeDoux, 1992;Freeman et al, 1997) and they join a growing body of data that has led to a recent resurgence of interest in the context processing role of the hippocampus (Chun and Phelps, 1999;Rosenbaum et al, 2001;Jeffery et al, 2004;Johnson, 2004;Smith et al, 2004;Weis et al, 2004;LaBar and Phelps, 2005;Shanks et al, 2005).…”
Section: What Constitutes a Context?supporting
confidence: 54%
See 4 more Smart Citations
“…In this way, the hippocampus could bias the behavioral expression systems of the brain . These results support context processing accounts of hippocampal function (Hirsh, 1974;Penick and Solomon, 1991;Kim and Fanselow, 1992;Phillips and LeDoux, 1992;Freeman et al, 1997) and they join a growing body of data that has led to a recent resurgence of interest in the context processing role of the hippocampus (Chun and Phelps, 1999;Rosenbaum et al, 2001;Jeffery et al, 2004;Johnson, 2004;Smith et al, 2004;Weis et al, 2004;LaBar and Phelps, 2005;Shanks et al, 2005).…”
Section: What Constitutes a Context?supporting
confidence: 54%
“…The spatial layout of an environment is a critical feature of any context and several authors have used the term ''spatial context'' to denote this relationship (Nadel et al, 1985;Jeffery et al, 2004). It has been suggested that spatial context coding is one example of the general context processing function of the hippocampus (Mizumori et al, in press;Smith et al, 2004;Smith and Mizumori, 2006). Indeed, the spatial representations seen in our studies were clearly dependent on nonspatial features of the context (Fig.…”
Section: Place Fields Are Part Of a Context Representationmentioning
confidence: 63%
See 3 more Smart Citations